Life strategies and adaptation of indigenous popolocas sugarcane migrant workers from Puebla to a shelter in Morelos Mexico - Sánchez Saldaña, Kim (2020)
We present research findings of the organization of a group of indigenous Popolocas sugarcane workers from Puebla who usually come to the harvest in Morelos. The importance of family strategies for social reproduction are analyzed, in the adaptation of these temporary migrant workers to adverse working and living conditions. It is important to consider the different cultural factors of the group for their analysis. In addition, the role of the traditional labor intermediary and leader of the group has been revealing, by representing the interests of the workers he is in charge of, which in turn makes possible the reproduction of their cultural identity.